Crashed ebook - Hallinan, Timothy (Junior Bender, 2012)
Quick-talking burglar Junior Bender gets blackmailed into becoming a private investigator for crooks in this first hilarious Hollywood mystery! “If you're looking for a mystery with a fresh new hero then you’ll want to run right out and get this book. It’s just fabulous.”  —NPR's Morning Edition   Junior Bender, a burglar with a magic touch, is being blackmailed into taking on a new freelance job. One of LA’s biggest crime bosses is producing a porn movie that someone keeps sabotaging; Junior’s job is to figure out who’s responsible and keep the movie on track. The trouble is, he’s not sure he can go through with the job, blackmail or no blackmail. The actress lined up to star in the film, Thistle Downing, is an ex-child star who now lives alone in a drug-induced stupor, destitute and uninsurable. This movie would be scandalous fodder for tabloids around the country. Junior knows what he should do—get Thistle out and find her some help—but doing the right thing will land him on the wrong side of some scary people.